ANALISIS RESEPSI “UNSUR KEKERASAN” DALAM VIDEO GAME AMONG US - Widyananda Putra , Ricky (Universitas Budi Luhur, 2021)
Gamers are an important element in video games. Those who encourage game developers to improve the quality of their products. One game that is currently being discussed is Game Among Us, this game is a game inspired by the Werewolf game. In the process of designing and developing a game concept, it is very important to know the users who are expected to play the designed game. One way to get to know the user can be done by studying and researching pre-existing games, so that the user process can understand the meaning of a game, this can be studied with various approaches, one of which is using reception analysis theory. This theory focuses on the activity of interpreting meaning, producing, and experiencing the audience's experience in interaction with media texts. Then those who will be respondents in this research are the creative box community, a game developer community forum that was established in 2016 consisting of students from Budi Luhur University, Jakarta who are directly engaged in producing games and as game media users, where the object of this research is in the form of game media. Therefore, researchers make creative boxes as research subjects by using the object of research, namely the game Among Us. So the goal to be achieved in this research is to find out the meaning of the game Among Us in the form of elements of violence, visualization of characters and backgrounds and storylines using a qualitative descriptive approach.